Student interest in participating individual counseling in senior high school 8 Padang - Nurhabibah Nurhabibah; Syahniar Syahniar; Netrawati Netrawati (Jurnal Neo Konseling, 2019)
Interests following individual counseling is a desire to attend individual counseling when experiencing problems in order to alleviate the problem. Reality in schools, during the school year 2018/2019 there were only 30 students who follow individual counseling of the overall number of students 602 people, including three students for counsel of their own accord while 27 other students for counsel being summoned by the BK teachers or students were handed over by homeroom or subject teachers / teachers picket. The purpose of this study is to describe the interest of students follow individual counseling services of aspects 1) attention, 2) interest, 3) the desire, 4) belief, and 5) action. This research is quantitative research with descriptive approach. The population of this research are students of class X and XI SMA N 8 Padang, amounting to 602 people. The sampling technique was conducted by using proportional random sampling. The research sample consists of 240 people. This study was conducted by administering research instruments scale model Likert. Data analyzed by descriptive statistical techniques. The research findings indicate 1) the students have a high attention to individual counseling, (2) students interested enough to attend individual counseling, (3) students quite willing to participate in individual counseling, (4) students have confidence high for individual counseling, and (5) the students are quite active in participation involved to follow individual counseling. Based on the findings of this study concluded that students in SMA N 8 Padang quite interested to attend individual counseling.